Effectiveness of Intraperitoneal Bupivacaine in General Anesthesia for Laparoscopic Appendectomy - Caverina, Sarah Lorenza; Rindiati, Fanda Ayyu; Respati, F.X. Andhi Haris (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Introduction: Appendicitis is an inflammation of vermiform appendix organ. It is a medical emergency case and one of the most common acute abdominal cases. The removal of acute appendix with minimally invasive surgery, laparoscopic procedure, is associated with shortened recovery time and length of stay in hospital, reduced risk of postoperative wound infections, also improved cosmetic outcomes. Anesthesia procedure for laparoscopic in Indonesia is usually performed under general anesthesia (GA) which has effective and safe form of sedation. One local anesthesia agent that often used in laparoscopic procedure is bupivacaine. Studies have shown that intraperitoneal bupivacaine as analgesia after laparoscopy can reduce postoperative pain, such as visceral pain associated with tissue injury and the stretching of nerve endings in the peritoneal cavity, parietal pain related to the incisional trauma at the port sites, and shoulder pain referred by stretching of the diaphragm.Case report: Mr. TA, 27 years old, his lower right abdomen hurt and he was diagnosed with acute appendicitis ASA II. Patients performed with laparoscopic procedure under general anesthesia. Fentanyl 2 mcg/kg, propofol 2 mg/kg, rocuronium 0.6 mg/kg, and sevoflurane 1 MAC, 50% FiO2 : 50% water, 4 lpm flow were administered. After 90 minutes of surgery, 40 cc of 0.5% intraperitoneal bupivacaine was administered. Patient was assessed for the NRS score within 30 minutes after laparoscopic procedure. The NRS score was 0.Conclusion: It has been reported a patient underwent laparoscopic appendicitis procedure received intraperitoneal bupivacaine as a postoperative analgesia which provided quicker recovery and good improvement of pain control without any significant negative consequences.